Synthesis and Structure–Activity Relationship Studies of Quinoxaline Derivatives as Aldose Reductase Inhibitors. Issue 12 (2nd October 2013) - Wu, Bobin; Yang, Yanchun; Qin, Xiangyu; Zhang, Shuzhen; Jing, Chaojun; Zhu, Changjin; Ma, Bing
<x xml:space="preserve">Abstract</x> ARIs for diabetes: A series of 2‐(3‐benzyl‐2‐oxoquinoxalin‐1(2H)‐yl)acetic acid derivatives were designed and synthesized as inhibitors of aldose reductase (AR), a novel target for the treatment of diabetes complications. Most of the derivatives proved to be potent and selective, with IC50 values in the low nanomolar to micromolar range.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>